Komunitas Makrozoobentos di Sungai Suir dalam Area Perkebunan Kelapa Sawit PT. Tidar Kerinci Agung - Muhammad Syahid Ridho; Izmiarti Izmiarti; Jabang Nurdin (Universitas Andalas, 2018)
The aim of this research was to know the composition and structure of macrozoobenthic community in Suir Stream at palm oil plantation area of PT. Tidar Kerinci Agung (TKA) has been conducted in February 2016 using survey method and purposive sampling technique in collecting data. Study sites consist of four stations based on condition around the stream. Macrozoobenthic community were sampled using surber net method with triplicate and accompanying physic-chemical measurements on each station. The results of this research show that 54 genera of macrozoobenthic were found consist of Insecta 44 genera, Oligochaeta 8 genera, Turbellaria and Gastropoda one genus respectively. The density of macrozoobenthic community range from 259.26-507.41 ind/m2 with average 381 ind/m2. The highest was found in station II dan the lowest was in station IV. The dominant genera (relative abundance > 10 %) in station I was Eukefferiella, station II Eukefferiella and Antocha, station III Tubificidae and Lumbriculus, station IV Eukiefferiella, Pseudocleon and Haplotaxis. The diversity of macrozoobenthic community was classified as moderate (H’= 1.25-2.94) and high equitability (E=0.54-0.84).